Model Manajemen Laba Akrual dan Riil Berbasis Implementasi International Financial Reporting Standards - Nurmala Ahmar; Nuraini Rokhmania; Agus Samekto (Journal of Accounting and Investment, 2016)
The aim of this study was to investigate the impact of inplementasi International Financial Reporting Standards (IFRS) on accrual earnings management and real earnings management. Adoption of accounting standards have an impact on the way of assessment, measurement and presentation. Samples are manufacturing companies listed in Indonesia Stock Exchange. Accrual earnings measurement method using five measurement approach, and three approaches to the measurement of real earnings management. The results showed that there were differences in real earnings management approach diskretioner costs and production costs. Three of the five methods used accrual earnings management (Modified Jones, Piecewise Linear and Kothari) proved to be the difference between before than after IFRS. While, Stubben Model not proved in this research. Results of this study are expected to have positive contribution on the development some policies related to the adoption of IFRS and the, particularly related to the accrual earnings management and real earnings management.